Debates, Challenges and Future Prospects of Federalism in Nepal: Contextual Implications of Provincial Governance - Sapkota, Mahendra (Rural Development Journal, 2026)
This paper analyses the implications and challenges of provincial governments in the context of Nepalese federalism. The study administered 420 questionnaires from all seven provinces of the country, with sixty each for primary data collection. The paper highlights the perception of the citizens of the provincial governments and some of the issues many provinces face. The research also shows that many people avoid dealing with the provincial levels and turn to the local ones, where it is possible or appeal to the federal capital for necessary services, which raises questions about the relevance of the provincial level. Despite limited opportunities in terms of proximity, service delivery, and leadership development, there is the belief that provincial governments are less accommodating of regional necessities and are perceived to run ineffective services in most cases. In addition, the involvement of the central government and the political instability that prevails at the provincial level obstruct good governance. The paper concludes that the effectiveness of federalism in Nepal depends upon the performance of provincial governments, which needs a severe revision, particularly in three areas, including strengthening the administrative capacities of provincial governments, improving the principles of governance and practices, and increasing the participation of the people. This underscores the urgent need for administrative reform, policy departure, party reformation, and leadership development to ensure the efficiency and effectiveness of provincial governments.